PENGENALAN STANDAR AKUNTANSI BERBASIS KOMPUTER DALAM MEWUJUDKAN DESA WISATA YANG MANDIRI - Lalu Takdir Jumaidi; Wirawan Suhaedi; Baiq Anggun Hilendri L. (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This subservience was done for human sources of tourism are not used optimally and the use of manual accounting is not effective and efficient in accommodating the development of the activities of village tourism. In addition, management and other institutions involved need financial report quickly and objectively. These phenomena are the result of the development of computer technology. The aim of this subservience is giving knowledge on businessman and development of village tourism finance through introducing computer-based accounting in order management and other institutions involved ready to take such policy. In accordance with the result of field survey, a more effective technique was by dissemination and guidance comprehensively on developing strategy for village tourism and introducing computer-based accounting in case of management activities of village tourism are able to be developed and be being an autonomous one. The finding was simple people having better comprehension on the use of computer-based accounting than manual.